Morphometric and genetic identification of Mackerel (Rastrelliger sp.) collected from Muara Baru Fish Market, Jakarta - Ummu Salma; Hawis Madduppa (Jurnal Ilmu Kelautan Kepulauan, 2021)
Ecosystems in Indonesia have a lot of potential resources, and one of them is seafood resources. Mackerel is potential catches of fish in the Jakarta Bay (as part of Java Sea area) that has high economic value. The Java Sea has only two mackerel species, Rastrelliger brachysoma and R. kanagurta which have similar morphology. Therefore in this study was conducted to compare morphometric and molecular analysis (DNA barcoding) using COI sequences so that specific species from specimens could be identified. The analyzed fish samples have striking characteristics such as blackline on the back, a black line near the pectoral fins, and a dark body part is extending above the rib line. The dorsal fins have a yellowish-gray color, yellowish pectoral, and pectoral fins.The result showed that measurements characteristic features of mackerels in Muara Angke belonging to Rastrelliger genera. DNA Barcoding analysis showed that the collected sample identified as Rastrelliger kanagurta with 99.25% identification similarity. The DNA code can distinguish between all fish species and identify the eggs, larvae, and carcass pieces of this species. So that fish in fish landings can be identified and tagged according to their species. This study has successfully identified a sample from Muara Angke by using a DNA code and therefore would be beneficial for managing food controlling and food safety concerns.Â Keywords: molecular identification, DNA barcoding, Rastrelliger kanagurta, morphological analysisÂ